A Study on the Comparison between Minimum Jerk and Minimum Energy of Nonlinear Dynamic Systems - Seneewong Na Ayuttaya, Suwimon; Veeraklaew, Tawiwat; Vichianlerd, Khemarin (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2006)
-